What is 3(x-4) = 2x - (3x - 4) ?

I tried to solve it but when i plug the numbers, both sides are unequal.

1 Answer
Nov 30, 2017

x=4

Explanation:

Start of by distributing the numbers. So, do this:

Actual Equation:
3(x-4)=2x-(3x-4)

Actual Equation after distributing the numbers:
3x-12=2x-3x+4

Notice how I multiplied the (x-4) with 3 and the (3x-4) with the -. If you want to take the parentheses out, multiply the quantity inside the parentheses with the number that is directly outside of the parentheses. ex: 3(x-4) or -(3x-4)

-(3x-4) became -3x+4 because the number that is outside of the parentheses is -1, therefore multiplying (3x-4) with -1 equals -3x+4.

Your second step would be to shift the x variables onto one side. I'm going to shift it to the left side.

3x-12=2x-3x+4

Step 3: Simplify the 2x-3x into -x

3x-12=-x+4

Step 4: Add x to each side

4x-12=4

Step 5: Add 12 to each side

4x=16

Step 6: Divide each number by 4

x=4